Structure‐Dependent Wear and Shear Mechanics of Nanostructured MoS2 Coatings. Issue 14 (3rd June 2020) - Serles, Peter; Sun, Hao; Colas, Guillaume; Tam, Jason; Nicholson, Eric; Wang, Guorui; Howe, Jane; Saulot, Aurélien; Singh, Chandra Veer; Filleter, Tobin
Abstract: Sputter‐deposited molybdenum disulfide coatings are one of the most common lubricants for extreme environments. However, their performance predictability remains limited by the complexity of van der Waals wear and shear mechanics in bulk materials resulting in unexpected premature failure. In the present study, two nanostructured MoS2 coatings of similar macroscopic properties are shown to exhibit entirely different wear and shear mechanics due to their nanostructure. Friction force microscopy with steel‐beaded cantilevers is used to measure the per‐cycle evolution of friction, wear, and topography in situ over the lubricant lifetime under an inert nitrogen environment. Molecular dynamics simulations confirm the subsurface structural failure mechanisms of the coatings under shear stress, and atomic force microscope phase imaging and Raman spectroscopy are used to identify tribofilm formation mechanics. The nanocrystal–amorphous composite structure shows improved wear resistance but at the cost of limited stress relaxation which creates high‐stress failure and fracture‐dominated wear. The purely nanocrystalline coating exhibits lower shear resistance but consistent stress relaxation by van der Waals cleavage and triple junction fracture which results in higher wear rates with predictable abrasion‐dominated failure. The contrast in nanoscale performance of the coatings allows for the lubricant nanostructure to be tuned for ideal applications for extreme environments. Abstract : In situ friction force microscopy and molecular dynamic simulations reveal the true wear and friction mechanics of two nanostructured MoS2 coatings when subjected to shear forces. Despite similar macroscopic mechanical properties, purely nanocrystalline and nanocrystal–amorphous coatings exhibit entirely different wear, crack propagation, and failure behavior.